KESALAHAN SISWA SEKOLAH DASAR DALAM MEREPRESENTASIKAN PECAHAN PADA GARIS BILANGAN - Suryowati, Eny (AKSIOMA JURNAL PENDIDIKAN MATEMATIKA, 2015)
Fraction is one of the complex material in elementary school. This study aims to describe how students represent fractions on a number line, and describes the mistakes made in the students represent fractions on the number line. This research is qualitative. Subjects in this study there are two students class V of SDN Tamping Mojo II. The data collection method using a task-based interviews. Instruments in this study is the researchers themselves and supporting instruments is a task sheet and interview guidelines. Based on this research, how subjects represent fractions on a number line: fractions with the same denominator on the number line, the subject of linking the amount of parts in the interval of 0 to 1 as the denominator, the subject of linking the amount of the line that divides the interval of 0 to 1 as the denominator, the subject of fractions sort of fractional numerator. Fractions with denominators are not the same on the number line, the subject of fractions with denominators sort biggest, subject to name a point regardless of its parts. Fractions on the number line at a specified point (the same parts and the parts are not the same), the first subject tends to count the number of lines that divide the number line into sections of the same count the number of parts that are formed to be the denominator, the second subject occurs misconceptions with jump number. Fractional mixture on the number line, the two subjects can not represent. Mistakes made by the two subjects are conceptual errors and application errors.